Answer:
![\text{ The solution of the system is }(4,1)](https://img.qammunity.org/2023/formulas/mathematics/college/u0v0eoyryhv8clc9u12ws8a7wnb3422su8.png)
Explanation:
The substitution method consists in isolating one of the variables and plugging it into the other equation. Given the following system of equations, solve for substitution:
![\begin{gathered} x=3y+1\text{ }(1) \\ 2x+4y=12\text{ }(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/yw0fwlwhu9csmaeteoh3qqhejw53bzfy8w.png)
Since ''x'' is already isolated in (1), plug it into equation (2):
![\begin{gathered} 2(3y+1)+4y=12 \\ \text{ Using distributive property:} \\ 6y+2+4y=12 \\ 10y+2=12 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/i91fyw2fquku2efgn2do2ovik6hb43lf1u.png)
Solve for y.
![\begin{gathered} 10y=10 \\ y=(10)/(10) \\ y=1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/1fqekvqjsezbt1br3pruwcpl4ick2gg6fa.png)
Now, knowing the y-value for the solution of the system. Substitute y=1 into equation (1):
![\begin{gathered} x=3y+1 \\ x=3(1)+1 \\ x=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hj2v104flk7zbydye5q7zdrbsvdqe9e71q.png)
![\text{ The solution of the system is }(4,1)](https://img.qammunity.org/2023/formulas/mathematics/college/u0v0eoyryhv8clc9u12ws8a7wnb3422su8.png)